2021
DOI: 10.3390/cells10010058
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose Tissue-Derived Mesenchymal Stromal Cells Inhibit CD4+ T Cell Proliferation and Induce Regulatory T Cells as Well as CD127 Expression on CD4+CD25+ T Cells

Abstract: Mesenchymal stromal cells (MSC) exert their immunomodulatory potential on several cell types of the immune system, affecting and influencing the immune response. MSC efficiently inhibit T cell proliferation, reduce the secretion of pro-inflammatory cytokines, limit the differentiation of pro-inflammatory Th subtypes and promote the induction of regulatory T cells (Treg). In this study, we analyzed the immunomodulatory potential of human adipose tissue-derived MSC (ASC), on CD4+ T cells, addressing potential ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 57 publications
2
29
1
Order By: Relevance
“…Importantly, we also demonstrated that the increased recruitment of Foxp3+Tregs in the retina correlated with dampened retinal inflammation and improved b-wave amplitudes in the I/R injury model. Our findings are in keeping with published data by others that have demonstrated Tregs act as part of the adaptive immune system, and thereby (A) serve as important regulators of inflammation and play a critical role in immune homeostasis [ 14 ]; (B) are inversely correlated with retinal ischemia [ 34 ]; and (C) are well known for immunomodulation, with recent evidence suggesting that MSCs can enhance Foxp3+Treg differentiation and stability from activated T cells in part through mitochondrial transfer [ 12 , 13 , 35 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Importantly, we also demonstrated that the increased recruitment of Foxp3+Tregs in the retina correlated with dampened retinal inflammation and improved b-wave amplitudes in the I/R injury model. Our findings are in keeping with published data by others that have demonstrated Tregs act as part of the adaptive immune system, and thereby (A) serve as important regulators of inflammation and play a critical role in immune homeostasis [ 14 ]; (B) are inversely correlated with retinal ischemia [ 34 ]; and (C) are well known for immunomodulation, with recent evidence suggesting that MSCs can enhance Foxp3+Treg differentiation and stability from activated T cells in part through mitochondrial transfer [ 12 , 13 , 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…The suppression of immune cell activation is one of the manifestations of MSC-mediated immunomodulation [ 12 , 26 ]. To assess whether mitochondrial transfer from stem cells to primary mouse splenocytes impacts T-cell differentiation, activated splenocytes were cocultured with iMSCs or ASCs and subsequently assessed for the expression of T regulatory cells ( Figure 5 A and Supplemental Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PBMCs were collected as described in a previous study (32). In brief, CD4 + T cells were isolated from PBMCs, and then CD4 + T cells were treated with 10 ng/ml IL-2 and 2 µg/ml anti-CD3/CD28 for 72 h in order to induce the activation of Treg cells (33).…”
Section: Reagents Emodin Was Purchased From Beijing Solarbiomentioning
confidence: 99%